Comparison of measuring methods of nitrogenisotope composition in coals - Zhao Fenghua; Cheng Chen; Fan Lijun; Guo Hong; Gu Shaoshun (矿业科学学报, 2018)
For improving the quality and reliability of nitrogen isotope in coals,this paper analyses and compares nitrogen isotope composition in a series of coal samples measured by Kjedahl-Rittenberg method and two Dumas combustion methods(containing EA-Conflo IV-IRMS method and sealed quartz tube combustion method),respectively.The results show that:① the precision of Kjedahl-Rittenberg method is not very ideal and nitrogen in coals cannot be completely extracted.This method is time-consumed relative to two other Dumas methods.② EA-Conflo IV-IRMS method is more convenient and efficient,especially for analyzing organic nitrogen isotope compositions of massive samples.The precision of measuring results mainly depend on the types of samples and the condition of the system.A reliable data could be got only after specific parameter optimization and subsequent corrections.For samples containing high contents of inorganic nitrogen,it is better to extract kerogen to measure.③ Sealed quartz tube method can extract nitrogen completely in coal samples with high precision and is easier to measure isotope compositions of bulk nitrogen,but also time-consumed for massive samples.